ANALISIS PENGARUH FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA TAHUN 2019-2022 - Herman, Atikah Pratiwi; Afni, Zalida; Sukartini (Journal of Applied Accounting And Business, 2023)
This study seeks to assess the impact of applying the Fraud Hexagon (comprising pressure, opportunity, rationalization, capability, arrogance, and collusion) on the likelihood of fraudulent financial statements within banking companies listed on the Indonesia Stock Exchange during the period from 2019 to 2022. Employing a quantitative approach, the research utilized purposive sampling, selecting a sample of 36 companies. Logistic regression analysis was conducted on the data using IBM SPSS 26 software. Fraudulent Financial Statements were identified through restatements in the sample companies' financial statements, serving as the dependent variable. The Fraud Hexagon elements were represented by variables such as financial target, ineffective monitoring, change in auditor, change in director, frequent appearance of CEO's image, and collaboration with government projects, serving as independent variables. The findings indicate that the change in auditor and collaboration with government projects have a significant impact on the potential for financial report fraud. However, variables such as financial target, ineffective monitoring, change of director, and frequent appearance of CEO's image were found to have no effect on the potential for financial report fraud.